Cognition and tool use: forms of engagement in human and animal use of tools - Baber, Christopher (London, 2003)
"The ability to use tools is a distinguishing feature of human beings. It represents a complex psychomotor activity which we are only now beginning to fully understand. Robust theoretical accounts are being developed which allows us to understand better how people use tools and which explain differences in human and animal tool-use from the perspective of cognitive science. Our understanding needs to be based on research into how people use tools, which draws on many disciplines: such as why tool use can fail (drawing particularly on ergonomics) and the neurological areas probably associated with tool use (drawing on neuropsychology). This book considers contemporary tool use in domains such as surgery, and considers future developments in human-computer interfaces, such as haptic virtual reality and tangible user interfaces."